Loss of MCL1 function sensitizes the MDA‐MB‐231 breast cancer cells to rh‐TRAIL by increasing DR4 levels. Issue 10 (25th March 2019) - De Blasio, Anna; Pratelli, Giovanni; Drago‐Ferrante, Rosa; Saliba, Christian; Baldacchino, Shawn; Grech, Godfrey; Tesoriere, Giovanni; Scerri, Christian; Vento, Renza; Di Fiore, Riccardo
Abstract: Triple‐negative breast cancer (TNBC) is a form of BC characterized by high aggressiveness and therapy resistance probably determined by cancer stem cells. MCL1 is an antiapoptotic Bcl‐2 family member that could limit the efficacy of anticancer agents as recombinant human tumor necrosis factor related apoptosis‐inducing ligand (rh‐TRAIL). Here, we investigated MCL1 expression in TNBC tissues and cells. We found MCL1 differentially expressed (upregulated or downregulated) in TNBC tissues. Furthermore, in comparison to the human mammary epithelial cells, we found that MDA‐MB‐231 cells show similar messenger RNA levels but higher MCL1 protein levels, whereas it resulted downregulated in MDA‐MB‐436 and BT‐20 cells. We evaluated the effects of rh‐TRAIL and A‐1210477, a selective MCL1 inhibitor, on cell viability and growth of MDA‐MB‐231 cells. We demonstrated that the drug combination reduced the cell growth and activated the apoptotic pathway. Similar effects were observed on three‐dimensional cultures and tertiary mammospheres of MDA‐MB‐231 cells. In MDA‐MB‐231 cells, after MCL1 silencing, rh‐TRAIL confined the cell population in the sub‐G0/G1 phase and induced a drop in the mitochondrial transmembrane potential. To understand the molecular mechanism by which the loss of MCL1 function sensitizes the MDA‐MB‐231 cells to rh‐TRAIL, we analyzed by real‐time reverse transcription polymerase chain reaction, the expression of genes related to apoptosis, stemness, cell cycle, and those involved in epigenetic regulation. Interestingly, among the upregulated genes through MCL1 silencing or inhibition, there was TNFRSF10A (DR4). Moreover, MCL1 inhibition increased DR4 protein levels and its cell surface expression. Finally, we demonstrated MCL1‐DR4 interaction and dissociation of this complex after A‐1210477 treatment. Overall, our findings highlight the potential MCL1‐roles in MDA‐MB‐231 cells and suggest that MCL1 targeting could be an effective strategy to overcome TNBC's rh‐TRAIL resistance. Abstract : MCL1 is an antiapoptotic Bcl‐2 family member that could limit the efficacy of anticancer agents as recombinant human tumor necrosis factor related apoptosis‐inducing ligand (rh‐TRAIL). Here, we demonstrated that the combination of rh‐TRAIL/A‐1210477 (a selective MCL1 inhibitor) drastically reduced cell growth and activated the apoptotic pathway both on three‐dimensional cultures and tertiary mammospheres of the MDA‐MB‐231 cells. We also demonstrated that loss of MCL1 function sensitizes MDA‐MB‐231 cells to rh‐TRAIL by DR4 regulation. Overall, our findings highlight the potential MCL1‐roles in MDA‐MB‐231 cells and suggest that MCL1 targeting could be an effective strategies to overcome triple‐negative breast cancer's rh‐TRAIL‐resistance.